Ba6(Bi1−xEux)9B79O138 (0 ≤ x ≤ 1): synergetic changing of the wavelength of Bi3+ absorption and the red-to-orange emission ratio of Eu3+. Issue 26 (9th June 2015) - Li, Qiaoqi; Cong, Rihong; Zhou, Xianju; Gao, Wenliang; Yang, Tao
Abstract : Ba6 (Bi1− x Eu x )9 B79 O138 : x Eu 3+ shows a simultaneous change in the wavelength shift of Bi 3+ absorption and red-to-orange emission ratio by varying x . Abstract : Very recently, a novel barium bismuth borate Ba6 Bi9 B79 O138 (BBBO ) was shown to be a new analogue of REBaB9 O16 (RE = rare earth), which is a family of excellent phosphor hosts, because it has two types of cationic positions suitable for bi- and tri-valent activators (or sensitizers). In this study, we prepared Eu 3+ -to-Bi 3+ substituted solid solutions Ba6 (Bi1− x Eu x )9 B79 O138 (0 ≤ x ≤ 1) and performed a systematic UV-photoluminescence investigation. As anticipated, efficient energy transfer occurs in the whole series of compounds and the majority of the energy absorbed by Bi 3+ was transmitted to Eu 3+, causing a great enhancement of Eu 3+ emission. More interestingly, the Eu 3+ -to-Bi 3+ substitution leads to a centrosymmetric-to-noncentrosymmetric transition of the local coordination symmetry of the trivalent cations due to the size difference between Eu 3+ and Bi 3+ . This is observed in the synergetic changing of the wavelength of Bi 3+ 1 S0 → 3 P1 absorption (excitation spectra) and the red-to-orange emission ratio (emission spectra) when changing x .BBBO is a new polyborate host with a freshly resolved structure whose interesting preliminary results suggest the further development ofBBBO -based phosphors.